Prognostic Value of Preoperative Hydronephrosis in Patients Undergoing Radical Nephroureterectomy for Upper Tract Urinary Carcinoma: A Systematic Review and Meta-Analysis - Ye, Tao; Yang, Xiaoqi; Lv, Peng; Liu, Haoran; Ye, Zhangqun (Frontiers in Oncology, 2020)
Background: Several recent publications have evaluated the prognostic value of preoperative hydronephrosis (HN) in patients with upper tract urinary carcinoma (UTUC). The aim of this meta-analysis was to explore the pooled effect of preoperative HN on the prognosis of UTUC patients treated with radical nephroureterectomy (RNU) based on current evidence. Methods: We performed a systematic search of Pubmed, Cochrane library, and Web of Science databases from inception to June 2020. The outcomes of interest included overall survival (OS), cancer-special survival (CSS), disease-free survival (DFS), and intravesical recurrence-free survival (IVRFS). Results: Twenty-two studies with a total of 7542 patients satisfied the eligibility criteria and were finally included in this meta-analysis. The percent of patients with preoperative HN varied in the eligible studies, ranging from 18% to 81%. The pooled results showed that preoperative HN was significantly associated with worse OS (P = 0.004), CSS (P < 0.001), and DFS (P = 0.005), but not IVRFS (P = 0.12). No obvious publication bias was detected by Begg’s test in all the analyses. Conclusions: The results drawn in our meta-analysis suggest that the presence of preoperative HN is associated with worse prognosis in patients treated with RNU for UTUC. Therefore, closer surveillance and more aggressive therapy may be needed for UTUC patients present with preoperative HN. Well-designed prospective studies are necessary to substantiate the prognostic value of HN in UTUC.